Intégration environnementale de l’éolien et régulation locale des conflits : l’action des collectivités territoriales dans l’Aude (France). - Élodie Valette (VertigO)
Since the end of 90’s, many windmills fields have emerged in the departement of Aude (France). These implementations or implementation projects have lead to the emergence of many conflicts. The opacity of the French national politics in matter of development of alternative energies (1), the lack of a clearly defined  politics of national and regional development (2) conduce the local institutions to answer the lack of legislation by writing several documents in order to define a institutional frame to the implementation of windmills. This paper aims to analyze the impact of these documents and to evaluate their capacity to organize the local and collective environmental integration of the wind energy.